STUDY OF TEACHER PERFORMANCE IN SOUTH SULAWESI THROUGH INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE - Yahya, Muh.; Hartini, Hartini; Elpisah, Elpisah (Jurnal Aplikasi Manajemen, 2019)
This research aimed to analyze the effect of self efficacy on the intrinsic motivation, the effect of the self efficacy on the teacher performance, the effect of the intrinsic motivation on the teacher performance, and the effect of self efficacy on the teacher performance through intrinsic motivation. The method used in the research was the path analysis with the Structural Equation Modeling (SEM) AMOS. The research result indicated that self efficacy had a positive and significant effect on intrinsic motivation, the self efficacy had an insignificant effect on the teacher performance, the intrinsic motivation had a positive and significant effect on the teacher performance, and the self efficacy had a positive and significant effect on the teacher performance through the intrinsic motivation. This finding will provide input for the school to recognize the importance of self efficacy and intrinsic motivation in the development of teacher performance. Further research and practical implications are discussed.